Mussel-inspired HA@TA-CS/SA biomimetic 3D printed scaffolds with antibacterial activity for bone repair - Ji, Cheng; Zhang, Chengcheng; Xu, Zeya; Chen, Yan; Gan, Yanming; Zhou, Minghui; Li, Lan; Duan, Qinying; Huang, Tingting; Lin, Jinxin (Frontiers in Bioengineering and Biotechnology, 2023)
Bacterial infection is a major challenge that could threaten the patient's life in repairing bone defects with implant materials. Developing functional scaffolds with an intelligent antibacterial function that can be used for bone repair is very important. We constructed a drug delivery (HA@TA-CS/SA)scaffold with curcumin-loaded dendritic mesoporous organic silica nanoparticles (DMON@Cur) via 3D printing for antibacterial bone repair. Inspired by the adhesion mechanism of mussels, the HA@TA-CS/SA scaffold of hydroxyapatite (HA) and chitosan (CS) is bridged by tannic acid (TA), which in turn binds sodium alginate (SA) using electrostatic interactions. The result showed that the HA@TA-CS/SA composite scaffold had a great compressive strength of 68.09 MPa. It displayed excellent degradation and mineralization capabilities with strong biocompatibility in vitro. Furthermore, the antibacterial test results indicated that the curcumin-loaded scaffold inhibited S.aureus and E.coli with 99.99% and 96.56% effectiveness, respectively. These findings show that 3D printed curcumin-loaded HA@TA-CS/SA scaffold has considerable promise for bone tissue engineering.